2021
DOI: 10.1021/acs.est.1c02479
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Heavy Metal Adsorption on Soil with Machine Learning and Mapping Global Distribution of Soil Adsorption Capacities

Abstract: Studying heavy metal adsorption on soil is important for understanding the fate of heavy metals and properly assessing the related environmental risks. Existing experimental methods and traditional models for quantifying adsorption, however, are time-consuming and ineffective. In this study, we developed machine learning models for the soil adsorption of six heavy metals (Cd(II), Cr(VI), Cu(II), Pb(II), Ni(II), and Zn(II)) using 4420 data points (1105 soils) extracted from 150 journal articles. After a compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(43 citation statements)
references
References 88 publications
0
37
0
Order By: Relevance
“…A total of 13 common ML algorithms (Table S4) were screened during the regression model development, including adaptive boosting (AdaB), bagging, DT, a deep neural network, extra trees, gradient boosting (GradientB), KNN, Lasso, linear regression (Lr), RF, Ridge, support vector regression, and XGBoost. As there are numerous research articles, official documentations, posts, forums, and tutorials about these algorithms, we decided not to give introductions to them here. Note that all of these algorithms (as well as the chemical representations) were selected based on the literature as they were commonly used by other studies for environmental engineering applications .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 13 common ML algorithms (Table S4) were screened during the regression model development, including adaptive boosting (AdaB), bagging, DT, a deep neural network, extra trees, gradient boosting (GradientB), KNN, Lasso, linear regression (Lr), RF, Ridge, support vector regression, and XGBoost. As there are numerous research articles, official documentations, posts, forums, and tutorials about these algorithms, we decided not to give introductions to them here. Note that all of these algorithms (as well as the chemical representations) were selected based on the literature as they were commonly used by other studies for environmental engineering applications .…”
Section: Methodsmentioning
confidence: 99%
“…The workflow of this study can be found in Figure . For those who have little ML knowledge, we recommend these reference papers, , which have step-by-step guidance for building ML models for general environmental applications.…”
Section: Introductionmentioning
confidence: 99%
“…Lead ion (Pb 2+ ) is one of the most toxic and frequently exposed heavy metals in the environment. It can disturb the distribution and contents of trace metal elements (e.g., Fe and Zn) in the human body and destroy the enzyme system of the human body, thus causing diseases like autonomic nerve dysfunction, anemia, nausea, and dizziness. Furthermore, Pb 2+ are easily bound by albumin protein, thus leading to detrimental effects in the body .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the direct harm to the human body, Pb 2+ also pollutes the water, destroys the growth of aquatic animals and plants, shows strong accumulation in the soil, penetrates into the root systems of plants, affects the growth and development of plants, and reduces plant chlorophyll, thus hindering plant photosynthesis which in turn affects the entire ecosystem . Therefore, efficiently removing Pb 2+ from water has become a hot topic in sustainable chemistry and engineering. …”
Section: Introductionmentioning
confidence: 99%
“…The presence of heavy metals in soil and groundwater has long been recognized as a contentious issue worldwide. Because of their inherent accumulative and nondegradable properties, heavy metals in soil and groundwater pose significant environmental risks (Guo et al, 2018;Vatandoost et al, 2018;Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%